2010
DOI: 10.1016/j.molcel.2010.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Strand Invasion Structures in the Inverted Repeat of Candida albicans Mitochondrial DNA Reveal a Role for Homologous Recombination in Replication

Abstract: Molecular recombination and transcription are proposed mechanisms to initiate mitochondrial DNA (mtDNA) replication in yeast. We conducted a comprehensive analysis of mtDNA from the yeast Candida albicans. Two-dimensional agarose gel electrophoresis of mtDNA intermediates reveals no bubble structures diagnostic of specific replication origins, but rather supports recombination-driven replication initiation of mtDNA in yeast. Specific species of Y structures together with DNA copy number analyses of a C. albica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
97
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(108 citation statements)
references
References 73 publications
10
97
1
Order By: Relevance
“…6b). The extension of signal in the HMW range could be explained by a failure of ClaI to cut at the newly replicated arm(s) of the Y molecules because of the presence of the single-strand DNA (ssDNA) gaps [48][49][50] . The ¼ 3), sae2D (n ¼ 4), sgs1D (n ¼ 3) and sae2D sgs1D (n ¼ 7) clones are shown.…”
Section: Resultsmentioning
confidence: 99%
“…6b). The extension of signal in the HMW range could be explained by a failure of ClaI to cut at the newly replicated arm(s) of the Y molecules because of the presence of the single-strand DNA (ssDNA) gaps [48][49][50] . The ¼ 3), sae2D (n ¼ 4), sgs1D (n ¼ 3) and sae2D sgs1D (n ¼ 7) clones are shown.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a more conciliatory model would predict that Mgm101 may promote strand invasion and error-free recombinational repair by an unconventional deployment of its strand annealing activity. mtDNA is rich in ssDNA stretches (57). Instead of invading dsDNA duplex, which is dependent on Rad51/RecA, the Mgm101-ssDNA nucleoprotein filaments may be directly annealed to these homologous single-stranded donor sequences.…”
Section: Discussionmentioning
confidence: 99%
“…S3B). Previously it had been shown that in vitro RNase H treatment of mtDNA replication intermediates removes RNA:DNA hybrids and leads to the appearance of simple-Y structures in 2D agarose gels (41,42). In accordance with a replicon-like structure, the bubble-shaped molecules were resistant to in vitro RNase H treatment and heat-induced branch migration.…”
Section: R-loops Promote Genome Instability and Noncanonical Replicationmentioning
confidence: 98%